2018
DOI: 10.1111/aos.13952
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive personality traits, psychological morbidity and coping strategies in chronic central serous chorioretinopathy

Abstract: Purpose ‘Type A’ behavioural characteristics and psychosocial stress have traditionally been associated with chronic central serous chorioretinopathy (cCSC). However, a characteristical personality profile could not be identified in these patients and the presumed association with stress is subject to controversy, due to a lack of convincing studies using validated measuring instruments. In this study, we aimed to assess maladaptive personality traits, psychological morbidity and coping strategies in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Thus, the result can get altered with the perspective of the patient. A study by van Haalen et al, agrees with our study finding suggesting that chronic CSC patient have many adaptive strategies and coping mechanisms to overcome stress and it is not necessarily the causative [28].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the result can get altered with the perspective of the patient. A study by van Haalen et al, agrees with our study finding suggesting that chronic CSC patient have many adaptive strategies and coping mechanisms to overcome stress and it is not necessarily the causative [28].…”
Section: Discussionsupporting
confidence: 93%
“…), as well as in a psychological questionnaire survey ( n = 86, data presented elsewhere) (van Haalen et al. ). For the present study, exclusion criteria were excessive alcohol intake (>21 units/week), the use of corticosteroids (both systemic and local) or sleep medication prior to the development or during the time–course of cCSC and either night shift work or travelling from another time zone in the 6 weeks prior to evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Further suspicion for the role of androgens in CSC comes from studies showing higher levels of urinary testosterone in patients with type A personalities, a potential risk factor for CSC (Zumoff et al 1984). However, the role of personality traits in CSC is still up for debate (van Haalen et al 2018a). Androgen receptors are present in the mammalian choroid and human RPE (Wickham et al 2000), and mRNA for 5-α reductase, the enzyme responsible for the conversion of testosterone to the more potent dihydrotestosterone has also been found (Rocha et al 2000).…”
Section: Androgensmentioning
confidence: 99%
“…Additionally, type A personality is a term that is not well-circumscribed and not often used in psychology nowadays (van Haalen et al 2018b). Further studies using validated personality questionnaires on personality traits have shown no link with maladaptive personality traits in CSC patients (van Haalen et al 2018a). Our experience from clinical practice does however suggest patients with CSC are often of above-average intelligence.…”
Section: Stress and Psychological Profilementioning
confidence: 99%